Analysis on Al-Nawawi’s Criticism on Al-Daraqutni’s Methodology in ‘Ilal Al-Hadith - Yaakob, Mohd Aizul; Shamsudin, Roshimah (European Publisher, 2019)
Al-Daraqutni was no stranger to the fraternity of past hadith scholars. Some scholars criticized his commentaries on several hadiths from the al-Sahihayn, particularly pertaining to al-Daraqutni’s mastery of the discipline of ‘ilal al-hadith. Al-Nawawi, one of the critics, considered al-Daraqutni’s methodology in hadith criticism to be corrupted and weak. This research, which is wholly qualitative, involving data collection through literary review, analyzes those criticisms and concludes on the question whether they coincide with al-Nawawi’s own views. The research findings show that al-Daraqutni’s methods was neither corrupted nor weak as alleged but had firm footing in the methodologies previously practiced by hadith scholars in ancient times.